Reflections of Medical Interns on Internship in Internal Medicine - Piryani, Rano Mal; Piryani, Suneel; Deo, Gopendra Prasad (Journal of Chitwan Medical College, 2019)
Background: Reflection and reflective practices are considered as one of the important components of medical education and imperative for self-directed lifelong learning. The objective of this study was to take reflections of interns what they learnt during posting in internal medicine and challenges they faced and what was gratifying moments. Methods: MBBS course in Nepal is of five and half years including one-year mandatory rotational internship of which 2 months posting in internal medicine. The Internship of first MBBS batch at Chitwan Medical College started in May 2015. At the end of last round of posting of first group within department of internal medicine, written reflections of all interns were taken. The data were streamlined manually and presented. Results: Interns updated and enhanced clinical, report interpretation, correlating clinical condition with lab reports, decision making, management, documentation, counselling and communication skills for a limited time posted in medical wards, OPD, ICU, CCU and hemodialysis unit. Some of the challenges were dealing patients with different attitude, to become responsible trustworthy doctor, responding to expectations of patient and family and to keep patient informed. When patient believes and trusts on us and happily returns home were among the gratifying moments mentioned by interns. In fact, students were not taught about reflection during 4 and half years of study Conclusions: Though interns reflected but approach was not systemic as they didn’t learn about reflection during course of study. Incorporate reflection as a teaching learning and assessment methods in curriculum, implement it and make reflective practice as core professional skill.